Intracranial thrombosed anastomosing hemangioma: Case report. Issue 2 (1st December 2019) - Bodman, Alexa; Goodman, Abigail; Olson, Jeffrey J.
Abstract : An anastomosing hemangioma is a relatively new diagnosis of a benign vascular lesion that is typically found in the genitourinary tract. On imaging, anastomosing hemangiomas have a broad differential diagnosis and can resemble malignant lesions such as angiosarcoma. Here we present a case of a 33‐year‐old male with seizures who on imaging was found to have a presumed recurrent intracranial meningioma. After surgical resection of his lesion, this case was pathologically diagnosed as having anastomosing hemangioma. To our knowledge, this is the first report of a case of a thrombosed anastomosing hemangioma located at intracranial and intradural region.